Sistem Keamanan Sepeda Listrik Menggunakan Fingerprint - Zhera putri yulianingsih (Depertment of Electrical Engineering University of Mataram, 2024)
Fingerprint sensor technology has been implemented in a security system for electric bicycles using Arduino IDE as the core of the system. The main components consist of a fingerprint sensor, relay, and buzzer. The fingerprint sensor is responsible for reading the enrolled fingerprint, while the relay serves as a switch to regulate the flow of electricity to the electric bicycle. This approach provides an innovative solution that enhances the security level of the electric bicycle by allowing users to only access the bicycle using an enrolled fingerprint. Thus, the system combines reliable security with user convenience. Based on this research, it was found that the security system using Arduino Uno ATMega328 microcontroller and fingerprint sensor works well, allowing only the registered owner to access the electric bicycle. This proves that the use of biometric technology such as fingerprint sensors can be an effective solution to improve the security of electric bicycles.